2015
DOI: 10.3390/biomedicines3040304
|View full text |Cite
|
Sign up to set email alerts
|

Enzyme-Linked Immunosorbent Spot Assay for the Detection of Wilms’ Tumor 1-Specific T Cells Induced by Dendritic Cell Vaccination

Abstract: Background: Despite recent advances in cancer immunotherapy and the development of various assays for T cell assessment, a lack of universal standards within immune monitoring remains. The objective of this study was to evaluate the enzyme-linked immunosorbent spot (ELISpot) assay in comparison with major histocompatibility complex-tetramer analysis in the context of dendritic cell (DC)-based cancer immunotherapy. Methods: The ELISpot assay was performed on peripheral blood mononuclear cells to assess reproduc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
16
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
2
1
1

Relationship

3
5

Authors

Journals

citations
Cited by 14 publications
(20 citation statements)
references
References 24 publications
2
16
0
Order By: Relevance
“…Other TAAs have also been utilized in DC vaccines as demonstrated by a recent phase I trial evaluating the safety and immunogenicity of Wilms' tumor (WT1) class I/II peptides based DC vaccine for patients with advanced CRC (41). This trial confirmed DC vaccine efficacy based on WT1 expression in tissue using immunohistochemistry and identification of WT1-specific cytotoxic T cells using the Enzyme-Linked Immunosorbent Spot (ELISPOT) assays (Mabtech, Nacka Strand, Sweden) (42). Interestingly, the DC vaccine immunity persisted for two years associated with a prolongation in survival.…”
Section: Vaccinesmentioning
confidence: 76%
“…Other TAAs have also been utilized in DC vaccines as demonstrated by a recent phase I trial evaluating the safety and immunogenicity of Wilms' tumor (WT1) class I/II peptides based DC vaccine for patients with advanced CRC (41). This trial confirmed DC vaccine efficacy based on WT1 expression in tissue using immunohistochemistry and identification of WT1-specific cytotoxic T cells using the Enzyme-Linked Immunosorbent Spot (ELISPOT) assays (Mabtech, Nacka Strand, Sweden) (42). Interestingly, the DC vaccine immunity persisted for two years associated with a prolongation in survival.…”
Section: Vaccinesmentioning
confidence: 76%
“…Dead cells were excluded via 7-AAD (BD Pharmingen) staining for flow cytometry. WT1 tetramer-positive CTLs were defined according to the following criteria: (1) comprising at least 0.02% of the CD3 + CD8 + subset of 50,000-100,000 lymphocytes and (2) forming a clustered but not diffuse population [38].…”
Section: Immune Monitoring For Wt1-ctlsmentioning
confidence: 99%
“…The presence of WT1 antigen-specific cytotoxic T cells (WT1-CTLs) is defined according to the following criteria: presence of greater than 0.02% WT1-positive CD8 + T cells among the 50,000-10,000 lymphocytes analyzed with no evidence of false positive cells and WT1-positive cell population being clustered but not diffused with slight modification, as previously described [64]. ELISPOT assays were performed to measure WT1-specific IFN-γ production by peripheral blood mononuclear cells (PBMCs).…”
Section: Immune Monitoringmentioning
confidence: 99%
“…ELISPOT assays were performed to measure WT1-specific IFN-γ production by peripheral blood mononuclear cells (PBMCs). The presence of WT-CTLs was defined according to the following criteria: presence of at least 15 WT1-specific spots per 1 × 106 PBMCs and at least 50% more WT1-specific spots than negative peptide (HIV peptide) spots [64].…”
Section: Immune Monitoringmentioning
confidence: 99%